Le centre de conservation et d’étude de Lons-le-Saunier : un modèle sans faille ? - Élise Cousin (In Situ)
The Worksite of the Center for Conservation and Studies of Lons-le-Saunier (France, Jura) was driven by the aim to be a positive energy building. In order to do so, many solutions have been brought out to regulate the climate in the most passive possible way, and not through energy-consuming devices. Our study, carried out few months after the inauguration of the building within the framework of the Master en Conservation Préventive of Paris I, tries to highlight the strengths and weaknesses of these large shared storage areas.